Alternative Estimation of Effective Young’s Modulus for Lightweight Aggregate Concrete LWAC - Meriem Fakhreddine Bouali; Hima Abdelkader (Fracture and Structural Integrity)
The prediction of effective mechanical properties of composite materials using analytical models is of significant practical interest in situations in which tests are impossible, difficult, or costly. Many experimental and numerical works are attempting to predict the elastic properties of Lightweight Aggregate Concrete (LWAC). In order to choose the optimized prediction composite model, the purpose of this paper is to appraise the effective Young’s modulus of LWAC using two-phase composite models. To this effect, results of previous experimental research have used as a platform, upon which, 07 two-phase composite models were applied. The outcomes of this comparative analysis show that not all two-phase analytical models can be directly used for predicting Young’s modulus of LWAC. The Hashin-Hansen and Counto2 models are in close concordance with the experimental Young’s modulus of all LWAC used for comparison in this study. Thus, the precision of this prediction model demonstrates its effectiveness and potential application as a model for Lightweight Aggregate Concrete. They were found more appropriate for reasonable prediction of elasticity modules of the LWAC.